2003
DOI: 10.1021/ic020607b
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Aluminum in the Calcium Silicate Hydrate (C−S−H) of Hydrated Portland Cements:  A High-Field 27Al and 29Si MAS NMR Investigation

Abstract: The calcium silicate hydrate (C-S-H) phase resulting from hydration of a white Portland cement (wPc) in water and in a 0.3 M NaAlO(2) solution has been investigated at 14 and 11 hydration times, respectively, ranging from 6 h to 1 year by (27)Al and (29)Si MAS NMR spectroscopy. (27)Al MAS NMR spectra recorded at 7.05, 9.39, 14.09, and 21.15 T have allowed a determination of the (27)Al isotropic chemical shift (delta(iso)) and quadrupolar product parameter (P(Q) = C(Q)) for tetrahedrally coordinated Al incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
211
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(244 citation statements)
references
References 35 publications
31
211
2
Order By: Relevance
“…The two other main resonances appear at approximately −80 and −86 ppm and originate from the SiQ 1 (disilicates or chain end groups) and SiQ 2 (middle groups in chains) units, respectively. 24 29 Si MAS-NMR spectrum of AAS sample (Fig. 4(C)) shows some non-negligible differences compared to that of PC sample.…”
Section: Si and 27 Al Mas-nmr Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The two other main resonances appear at approximately −80 and −86 ppm and originate from the SiQ 1 (disilicates or chain end groups) and SiQ 2 (middle groups in chains) units, respectively. 24 29 Si MAS-NMR spectrum of AAS sample (Fig. 4(C)) shows some non-negligible differences compared to that of PC sample.…”
Section: Si and 27 Al Mas-nmr Analysismentioning
confidence: 92%
“…The second one at 8 ppm could correspond to the isotropic chemical shift of the monosulfate phase, C 4 AŜH 12 (δ iso = 11.8 ppm), and of the tetracalcium aluminate hydrate phase, C 4 AH 13 (δ iso = 10.2 ppm) (the chemical shift difference can be due to a large amount of disorder as these two phases are unobserved by XRD). 24,25 27 Al MAS-NMR spectrum of AAS sample is very different (Fig. 3(C)); it shows a major content of tetrahedrally coordinated Al in connection with the large band centred at 59 ppm and a lower amount of octahedrally coordinated Al related to the band at 8 ppm.…”
Section: Si and 27 Al Mas-nmr Analysismentioning
confidence: 97%
“…The 1 H- 29 Si cross polarization spectrum of CASM showed a broad nondistinct peak similar to that of the 29 Si MAS spectrum. This indicates that the Si phase contains OH groups or water molecules in the immediate vicinity of the silicon atoms.…”
Section: Casm Characterization (A) X-ray Analysis Of Casm (mentioning
confidence: 66%
“…Replacement of one or more Si atoms by Al atoms in the outer coordination sphere ofaQ n unit results in lower field shifts (i.e., less negative δ values), arising from deshielding. A signal maximum at 103 ppm for the chemical shift distribution of the CASM 29 Si spectrum showed that the silicate groups are primarily organized in three-dimensional networks of Q 3 (-95 to -103 ppm), Q 4 (-103 to -120 ppm), and Q 4 (1 Al) (-97 to -108 ppm) silicate tetrahedra. Small fractions of silicon were present as Q 3 (1 Al) (-89 to -97 ppm) and Q 2 (-85 to -95 ppm) environments.…”
Section: Casm Characterization (A) X-ray Analysis Of Casm (mentioning
confidence: 99%
“…These bands remain in the hydrated samples, although with a reduced intensity, indicating that a significant fraction of unreacted material is still present in these cements, consistent with the early age of the cementitious grouts studied here. Upon hydration, new bands centered at -81 ppm and -85 ppm are observed, and these are assigned to the Q 2 (1Al) and Q 2 sites typically identified in C-A-S-H type products 23 . This confirms that even at early ages of curing, the main binding phase forming in the BFS-PC grout is an…”
Section: Preprint Version Of Accepted Article Please Cite As: N Mobmentioning
confidence: 92%